2020
DOI: 10.1002/prca.201900083
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics and Weighted Correlation Network Analysis of Tear Samples in Type 2 Diabetes Patients Complicated with Dry Eye

Abstract: PurposeDiabetic patients are more likely to experience dry eye (DE). TMT‐based proteomics and WGCNA are used to identify the differentially expressed proteins in tear proteome of type 2 diabetes with DE. The aim is to provide a molecular basis for exploring possible mechanisms underlying the pathogenesis of diabetic DE.Experimental designSubjects are divided into four groups (ten in each): type 2 diabetes with DE; type 2 diabetes without DE; non‐diabetes with DE and normal controls. All subjects undergo DE tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Basal tear flow (Schirmer test II) and TBUT were found to be unaffected. These data are consistent with the observation that diabetic neuropathy most often involves the ophthalmic nerve, thus triggering a corneal neuropathy with loss of sensitivity [39,40], which in turn results in decreased tear secretion and altered composition of tear proteins [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Basal tear flow (Schirmer test II) and TBUT were found to be unaffected. These data are consistent with the observation that diabetic neuropathy most often involves the ophthalmic nerve, thus triggering a corneal neuropathy with loss of sensitivity [39,40], which in turn results in decreased tear secretion and altered composition of tear proteins [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Not discovering abnormally expressed gene signatures, WGCNA can assign highly correlated genes into the same coexpression module and identify clinical phenotype-related modules, which is more effective to identify diagnostic and therapeutic markers [ 9 ]. Recent studies have identified shared susceptibility modules and genes of diabetes and other diseases such as Alzheimer's disease [ 10 ], cardiovascular disease [ 11 ], and dry eye [ 12 ] utilizing WGCNA approach. Least Absolute Shrinkage and Selection Operator (LASSO) represents a popular technology, which is extended and broadly utilized to construct diagnostic and prognostic Cox proportional hazard regression models based on transcriptome profiles [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of these two genes supports the conclusion that 9,10-PQ treatment increased glycolysis capacity, as described above, and suggests that 9,10-PQ influenced osmotic pressure in fish liver. DNAJC3A and HYOU1, as members of heat shock proteins (HSP), are potential biomarkers of diabetes (92) and endoplasmic reticulum stress (61). Moreover, HYOU1 and NLRC3 play roles in proliferation and inflammation in cancer cells, and NLRC3 has been shown to be significantly downregulated in cancer tissues (38,90).…”
Section: Resultsmentioning
confidence: 99%